Producing high quality carbide-derived carbon from low quality byproducts stemming from SiC production - Ariyanto, Teguh; Mohd Laziz, Afiq; Gläsel, Jan; Zhang, Guirong; Garbes, Josef; Etzold, Bastian (Chemical Engineering Journal, 2016)
The utilization of carbide-derived carbons (CDCs) in a wide range of applications is obstructed due to relatively high production costs. In this study a possibility to reduce the costs of CDC synthesis by employing low quality SiC byproducts stemming from the ESK process is presented. While the crystallinity and impurity content differs for the different precursor qualities, the resulting CDC materials possess similar textural characteristics and carbon microstructures. Evaluation of intrinsic kinetic data reveals that the low grade precursors react faster during reactive extraction and can be best described by a power law approach. The CDC materials were further investigated with respect to their performance as electrode materials in Electric Double Layer Capacitors (EDLC). All SiC-CDCs display a comparable and excellent specific capacitance of approx. 115Fg-1. The results are demonstrating the promising utilization of CDC materials synthesized from low valuable SiC feedstock.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Carbide-derived carbon; ESK process; Kinetic study; Reactive extraction